The Positive and Negative Affect Schedule (PANAS) among Mexican married persons from Monterrey - José Moral (Interacciones, 2019)
The objective of the article is to study the internal consistency, construct validity, and distribution the Positive and Negative Affect Schedule (PANAS) among Mexican married persons. A sample of 727 participants (52.8% women and 47.2% men) was collected by random routes in Monterrey and its metropolitan area, Mexico. The PANAS, the Relationship Assessment Scale, and the Balanced Inventory of Desirable Responding were applied. The overall internal consistency was excellent. The PANAS presented a two-factor structure. By dropping item 12, a from-good-to-adequate fit and a good fit-parsimony relationship were achieved. The internal consistency of Positive Affect (PA) factor was excellent, and the one of Negative Affect (NA) factor was good. The distribution of the total score (Affective Intensity = AI) followed a normal curve. The central tendency in AI, PA and NA was equivalent between men and women. PA was correlated with marital satisfaction with a strong strength of association, NA with a moderate strength of association, and AI weak. Social desirability had a small effect size on PA and NA, and trivial on AI. It is concluded that the two-factor model is validated, and the PANAS presents internal consistency and concurrent construct validity.